Predicting interfacial hot-spot residues that stabilize protein-protein interfaces in oligomeric membrane-toxin pores through hydrogen bonds and salt bridges. Issue 1 (2nd January 2021) - Desikan, Rajat; Maiti, Prabal K.; Ayappa, K. Ganapathy
Abstract: Pore forming toxins (PFTs) are proteins which form unregulated oligomeric pores on target plasma membranes to cause ion leakage and cell death and represent the largest class of bacterial virulence factors. With increasing antibiotic-resistant bacterial strains, alternate therapies are being developed to target toxin pore formation rather than the bacteria themselves. One strategy is to undermine the stability of these multimeric pores, whose subunits are held together by complex amino acid interaction networks, by identifying key residues in these networks which could be plausible drug or mutagenesis targets. However, this requires a quantitative assessment of per residue contributions towards pore stability, which cannot be reliably gleaned from static crystal/cryo-EM pore structures. In this study, we overcome this limitation by developing a computational screening algorithm that employs fully atomistic molecular dynamics simulations coupled with energy-based screening that can predict 'hot-spot' residues which engage in persistent and stabilizing hydrogen bonds or salt bridges across protein-protein interfaces. Application of this algorithm to prototypical α -PFT (cytolysin A) and β -PFT ( α -hemolysin) membrane-inserted pores yielded a small predicted set of highly interacting residues, blocking of which could destabilize pore complexes. Previous mutagenesis studies validate some of our in silico predictions. The algorithm could be applied to all pores with known structures to generate a database of destabilizing mutations, which could then serve as a basis for experimental validation and rational structure-based inhibitor design. Communicated by Ramaswamy H. Sarma